Occurrence, distribution, and seasonality of emerging contaminants in urban watersheds. (June 2018) - Bai, Xuelian; Lutz, Alex; Carroll, Rosemary; Keteles, Kristen; Dahlin, Kenneth; Murphy, Mark; Nguyen, David
Abstract: The widespread occurrence of natural and synthetic organic chemicals in surface waters can cause ecological risks and human health concerns. This study measured a suite of contaminants of emerging concern (CECs) in water samples collected by the U.S. Environmental Protection Agency Region 8 around the Denver, Colorado, metropolitan area. The results showed that 109 of 144 analyzed pharmaceutical compounds, 42 of 55 analyzed waste-indicator compounds (e.g., flame retardants, hormones, and personal care products), and 39 of 72 analyzed pesticides were detected in the water samples collected monthly between April and November in both 2014 and 2015. Pharmaceutical compounds were most abundant in the surface waters and their median concentrations were measured up to a few hundred nanograms per liter. The CEC concentrations varied depending on sampling locations and seasons. The primary source of CECs was speculated to be wastewater effluent. The CEC concentrations were correlated to streamflow volume and showed significant seasonal effects. The CECs were less persistent during spring runoff season compared with baseflow season at most sampling sites. These results are useful for providing baseline data for surface CEC monitoring and assessing the environmental risks and potential human exposure to CECs. Highlights: Emerging contaminants were monitored in an urban watershed for two years. 109 of 144 analyzed pharmaceutical compounds were detected. 42 of 55 analyzed waste-indicator compounds were detected. 39 of 72 analyzed pesticides were detected. Emerging contaminants showed clear spatial variability and seasonality.